Effects of long-term exposure to ambient fine particulate matter on diabetes mellitus and the moderating effects of diet - Wang, Jinxia; Shi, Yunhao; Wang, Dongshuai; Dong, Xuehao; Zhang, Hanqing; Zhou, Sijie; Zhao, Yi; Zhang, Yuhong; Zhang, Yajuan (Huan jing yu zhi ye yi xue = Journal of environmental & occupational medicine, 2024)
Background Long-term exposure to ambient fine particulate matter (PM2.5) may increase the risk of diabetes, and a healthy diet can effectively control fasting blood glucose levels. However, it is unclear whether dietary factors have a moderating effect on the risk of diabetes associated with atmospheric PM2.5 exposure. Objective To investigate the association between long-term exposure to PM2.5 and diabetes in rural areas of Ningxia, and potential interaction of long-term exposure to atmospheric PM2.5 and diet on diabetes. Methods The study subjects were selected from the baseline survey data of the China Northwest Cohort-Ningxia (CNC-NX) , a natural population cohort. A total of 13917 subjects were included, excluding participants with missing covariate information. We utilized the annual average ambient PM2.5 concentration from 2014 to 2018 as the long-term exposure level. Logistic regression and multiple linear regression were employed to analyze the associations of long-term atmospheric PM2.5 exposure with diabetes and fasting blood glucose levels. Stratification by frequency of vegetable consumption, frequency of fruit consumption, and salty taste was used to examine moderating effects on the diabetes risk associated with atmospheric PM2.5 exposure. Results The mean age of the 13917 subjects was (56.8±10.0) years, and the prevalence of diabetes was 9.8%. Between 2014 and 2018, the average annual concentration of PM2.5 was (38.10±4.67) μg·m−3. The risk (OR) of diabetes was 1.018 (95%CI: 1.005, 1.032) and the fasting blood glucose was increased by 0.011 (95%CI: 0.004, 0.017) mmol·L−1 for each 1 μg·m−3 increase in PM2.5 concentration. Compared to those who consumed vegetables < 1 time per week, individuals who consume vegetables 1-3 times per week and ≥4 times per week had a reduced risk of developing diabetes by 27.1% (OR=0.729, 95%CI: 0.594, 0.893) and 16.8% (OR=0.832, 95%CI: 0.715, 0.971) respectively. Similarly, when compared to those who consumed fruits <1 time per week, individuals who consumed fruits 1-3 times per week and ≥4 times per week exhibited a reduced risk of diabetes by 16.4% (OR=0.836, 95%CI: 0.702, 0.998) and 18.2% (OR=0.818, 95%CI: 0.700, 0.959) respectively. Fasting blood glucose decreased by 0.202 (95%CI: -0.304, -0.101) mmol·L−1 in participants who ate vegetables 1-3 times per week. The effect of salty taste on diabetes and fasting blood glucose was not significant. The results of stratified analysis by dietary factors and PM2.5 concentration showed that the risks of diabetes were increased in the low PM2.5 pollution-low vegetable intake frequency group and the high PM2.5 pollution-low vegetable intake frequency group compared with the low PM2.5 pollution-high vegetable intake frequency group, with OR values of 3.987 (95%CI: 2.943, 5.371) and 1.433 (95%CI: 1.143, 1.796) respectively. The risk of diabetes was 50.1% higher in participants with high PM2.5 pollution and low fruit intake frequency than in participants with low PM2.5 pollution and high fruit intake frequency (OR=1.501, 95%CI: 1.171, 1.926). No interaction was found between salty taste and PM2.5 on diabetes. Conclusion Long-term exposure to ambient PM2.5 is associated with an increased fasting blood glucose and an elevated risk of diabetes in rural Ningxia population. Increasing the frequency of weekly consumption of vegetables or fruits may have a certain protective effect against diabetes occurrence, as well as a moderating effect on diabetes and fasting blood glucose levels associated with long-term exposure to atmospheric PM2.5